Source data for a study exploring production impacts of a 100% organic conversion in England and Wales - Smith, Laurence G.; Jones, Philip; Kirk, Guy J. D.; Pearce, Bruce; Williams, Adrian (Cranfield University, 2018)
Underlying data for ‘Modelling the production impacts of a widespread conversion to organic agriculture in England and Wales’ by L.G. Smith et al. (2018). We develop and apply a bespoke model, the Optimal Land Use Model (OLUM) to estimate levels of production from agriculture in England and Wales under organic management . Outputs under a range of scenarios are compared to the real-world distribution of conventional production in 2010.
Keywords: linear programming'; 'organic'; 'food security assessments'; 'modelling estimates'; 'land use activities'; 'Agricultural methods'; 'Agricultural Production Systems Simulation'; 'Agricultural Systems Analysis and Modelling'; 'Farming Systems Research'; 'Sustainable Agricultural Development'